Anesthesia mumps with airway obstruction after radical nephrectomy: A case report and literature review - Li, Wanqiang; Liao, Zhengquan; Yao, Ling; Zhang, Lusheng; Li, Xuesong; Dong, Ziqiang (Frontiers in Surgery, 2023)
Anesthesia mumps has rarely been reported. This article presents the diagnosis and treatment of a case of anesthesia mumps with airway obstruction in the urology department and reviews previous cases of the disease. A 58-year-old man had a history of hypertension and diabetes. He underwent laparoscopic radical nephrectomy for a right renal tumor. Postoperatively, a swelling of approximately 5×4 cm was observed in the left parotid region and left eyelid, and no palpable crepitation was detected. Enhanced computed tomography of the head and neck revealed obvious swelling of the laryngopharyngeal airway, and electronic laryngoscopy showed narrow airway. Laboratory test results including white blood cell count, C-reactive protein, serum amylase, and lipase levels were normal. The salivary culture from Stensen’s duct was negative. The patient was managed with endotracheal intubation and a ventilator to maintain breathing along with anti-infection, expectorant, and symptomatic treatment. The swelling left parotid gland gradually resolved without recurrence, and the patient was extubated on the 7th postoperative day. In this case, the pathophysiology of anesthesia mumps may have been related to the incorrect positioning of the thick short neck and the use of a head ring, which can result in the squeezing of vessels. In most cases, the salivary gland swelling resolves with observation and symptomatic treatment. In patients with anesthesia mumps, emergency airway management and careful observation are necessary if upper airway obstruction occur. This case report should increase awareness of anesthesia mumps and its complications among anesthesiologists, surgeons, and postoperative caregivers.